Rewilding wetlands: beaver as agents of within-habitat heterogeneity and the responses of contrasting biota. (22nd October 2018) - Willby, Nigel J.; Law, Alan; Levanoni, Oded; Foster, Garth; Ecke, Frauke
Abstract : Ecosystem engineers can increase biodiversity by creating novel habitat supporting species that would otherwise be absent. Their more routine activities further influence the biota occupying engineered habitats. Beavers are well-known for transforming ecosystems through dam building and are therefore increasingly being used for habitat restoration, adaptation to climate extremes and in long-term rewilding. Abandoned beaver ponds (BP) develop into meadows or forested wetlands that differ fundamentally from other terrestrial habitats and thus increase landscape diversity. Active BP, by contrast, are superficially similar to other non-engineered shallow wetlands, but ongoing use and maintenance might affect how BP contribute to aquatic biodiversity. We explored the 'within-habitat' effect of an ecosystem engineer by comparing active BP in southern Sweden with coexisting other wetlands (OW), using sedentary (plants) and mobile (water beetles) organisms as indicators. BP differed predictably from OW in environmental characteristics and were more heterogeneous. BP supported more plant species at plot (+15%) and site (+33%) scales, and plant beta diversity, based on turnover between plots, was 17% higher than in OW, contributing to a significantly larger species pool in BP (+17%). Beetles were not differentiated between BP and OW based on diversity measures but were 26% more abundant in BP. Independent of habitat creation beaver are thus significant agents of within-habitat heterogeneity that differentiates BP from other standing water habitat; as an integral component of the rewilding of wetlands re-establishing beaver should benefit aquatic biodiversity across multiple scales. This article is part of the theme issue 'Trophic rewilding: consequences for ecosystems under global change'.